Corticosteroids and glaucoma: How do treatments trigger ocular nerve damage? - A systematic literature review - Putra, I Gede Satya Wijaya; Adnyana, I Made Dwi Mertha; Wahyudi, I Wayan; Suardana, Anak Agung Komang; Indrayanti, Ni Komang Rina; Prabowo, Sang Kompyang Yudistira Eddy; Panduyasa, I Gede; Widyantari, Dewa Ayu; Agustini, Desak Gede Dwi; Suwandani, Ni Made Ayu (PT. Mega Science Indonesia, 2024)
Corticosteroids are steroid hormone derivatives produced by the adrenal glands. Corticosteroids in the health sector have been widely utilized as anti-inflammatory agents because of their strong and rapid effects. This study aimed to identify the impact of long-term corticosteroid use on eye damage. This study uses a systematic literature review, which is guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to the article screening process. The data of this study, in the form of demographic variables, route of administration, steroid type, comorbidities, and patient risk factors, were descriptively analyzed. As a result, 15 of the 22 articles were selected for analysis. Chronic corticosteroid administration may precipitate optic neuropathy, manifesting as glaucoma, which is characterized by progressive structural degeneration of retinal ganglion cells (RGCs) and concomitant visual function deterioration. The locus of primary pathological insult in glaucomatous conditions is the optic nerve head, specifically at the optic disc. This anatomical site is notable for the abrupt 90-degree angular deviation of RGC axons as they transition from the retinal nerve fiber layer to their trajectory within the optic nerve proper. The use of corticosteroids can damage ocular nerve tissue through an increase in intraocular pressure (IOP) beyond 21 mmHg. This increase in IOP is due to changes in the microstructure of the trabeculum webbing, resulting in increased obstruction to the outflow of aqueous humor.